KAJIAN YURIDIS KERUGIAN KEUNGAN NEGARA AKIBAT KORUPSI DAN KORELASINYA DENGAN HAK WARGA NEGARA - Anderson Umbu Yawang; Fransiskus Saverius Nurdin; Ernalinda Ndakularak (SUPREMASI HUKUM, 2023)
The practice of criminal acts of corruption in Indonesia is getting more and more apprehensive day by day. This thesis is supported by data 2019 to 2021 released by ICW that corruption practices have increased significantly, causing state financial losses reaching up to IDR 51.928 trillion. The problem of this study is how the correlation of state financial losses due to the practice of criminal acts of corruption by corruptors with the fulfillment of citizens' rights as constitusional rigts but not human rights. This research is a doctrinal legal research with a statutory and conceptual approach. This study concludes that there is an absolute correlation between state financial losses and the non-fulfillment of citizen rights such as work and a decent living. Keywords: Corruption; State Financial Losses; the Citizen’s Right.